Antioxidant, antiradical, and anticholinergic properties of cynarin purified from the Illyrian thistle (Onopordum illyricum L.). (3rd March 2016) - Topal, Meryem; Gocer, Hulya; Topal, Fevzi; Kalin, Pınar; Köse, Leyla Polat; Gülçin, İlhami; Çakmak, Kader C.; Küçük, Murat; Durmaz, Lokman; Gören, Ahmet C.; Alwasel, Saleh H.
Abstract: Cynarin is a derivative of hydroxycinnamic acid and it has biologically active functional groups constituent of some plants and food. We elucidated the antioxidant activity of cynarin by using different in vitro condition bioanalytical antioxidant assays like DMPD +, ABTS +, , DPPH and H2 O2 scavenging effects, the total antioxidant influence, reducing capabilities, Fe 2+ chelating and anticholinergic activities. Cynarin demonstrated 87.72% inhibition of linoleic acid lipid peroxidation at 30 µg/mL concentration. Conversely, some standard antioxidants like trolox, α-tocopherol, butylated hydroxytoluene (BHT), and butylated hydroxyanisole (BHA) exhibited inhibitions of 90.32, 75.26, 97.61, 87.30%, and opponent peroxidation of linoleic acid emulsion at the identical concentration, seriatim. Also, cynarin exhibited effective DMPD +, ABTS +, , DPPH, and H2 O2 scavenging effects, reducing capabilities and Fe 2+ chelating effects. On the contrary, IC50 and Ki parameters of cynarin for acetylcholinesterase enzyme inhibition were determined as 243.67 nM ( r 2 : 0.9444) and 39.34 ± 13.88 nM, respectively. This study clearly showed that cynarin had marked antioxidant, anticholinergic, reducing ability, radical-scavenging, and metal-binding activities.